(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2025)
The usage of herbicides is essential to sustain agricultural productivity throughout the world. Plants have natural mechanisms to detoxify herbicides where the most important steps are catalyzed by certain enzymes such as cytochrome P450 mono-oxygenases (CYPs) (catalyze oxidation reactions) and glutathione transferases (GSTs) (conjugate electrophilic herbicides with the tripeptide glutathione (GSH). The GST/GSH system has been found to play a major role in the detoxification of several classes of herbicides and therefore in the herbicide-resistance mechanism of weeds. GST structures have been determined experimentally in Zea mays, Arabidopsis thaliana, Glycine max, etc. that provide structural and functional insights on xenobiotics detoxification on rice. There is a lot of unexplored space regarding the structure and ligand binding specificity of rice GSTs in plants. In this study, we have analyzed the rice GSTs of various classes and have modeled their structure to understand their conserved nature. It is important to understand the similarity and their interaction pattern with herbicides observed among the diverse class of GSTs expressed in the rice. Rice genomic data available in public databases were used to predict the conserved and variable regions in rice GSTs. Sequence-wise comparison of 79 GST sequences categorized all the seven GST classes separately and no similarity between them was observed. Structure comparison reported similarity between the Phi and Theta classes having the least RMSD value of 1.195Åwhereas the Dhar and Phi classes were highly diverging with the highest RMSD value of 3.051Å. The docking result showed the higher affinity of glutathione, and chlorsulfuron herbicide towards ZETA protein compared to other GST classes. Further alanine mutation analysis reported the higher binding efficiency upon mutating ARG 24 and TYR 102 amino acids towards the binding of chlorsulfuron herbicide, respectively. Molecular dynamics simulation using GROMACS was successful in capturing the dynamics of the alanine mutated Zeta-Chlorsulfuron complexes, and the stable behavior of the complex may have implications for the herbicide detoxification process.